Botox rechallenge—An additional tool in the management of an incompletely emptying bladder and inadequate overactive symptom control following sacral neuromodulation. Issue 1 (16th June 2020) - Timm, Brennan; Jayarajan, Jyotsna; Chan, Garson; Bolton, Damien
Abstract: Two female patients aged 70 and 72 with video‐urodynamics‐confirmed detrusor overactivity and detrusor underactivity (DO‐DU) were treated. Patients were refractory to medical therapies and had previously failed intravesical botulinum toxin type A (BoNT‐A) at other centers secondary to urinary retention and difficulty with self‐catheterization. Placement of an Interstim II device (Medtronic, Minneapolis, Minnesota) for sacral neuromodulation (SNM) as alternative third‐line treatment partially improved overactive bladder (OAB) symptoms while significantly improving voiding symptoms. Postvoid residual (PVR) of patients improved from a median of 118 mL (110‐125 mL) to 20 mL (18‐26 mL) and 213 mL (195‐230 mL) to 70 mL (60‐73 mL), respectively. Addition of medical therapies post SNM failed to modify OAB symptoms further and a rechallenge with dose‐reduced BoNT‐A was undertaken.OAB symptoms were significantly improved by addition of BoNT‐A, while urinary retention was avoided (median PVR post BoNT‐A 38 mL [34‐40 mL] and 185 mL [150‐205 mL], respectively). Reduction in incontinence pad use as well as resolution of nighttime incontinence in both patients and daytime incontinence in one patient was achieved. DO‐DU patients treated by SNM who have improved bladder emptying (PVR <100 mL) but incomplete resolution of OAB symptoms should be trialed on adjunct medical therapies to improve OAB symptoms. If OAB symptoms are still inadequately controlled, consideration of a rechallenge with BoNT‐A, particularly with dose reduction, appears to be efficacious and avoids symptomatic retention in this challenging cohort.